Digitalisasi UMKM Desa Lekis Rejo melalui Pemetaan Usaha untuk Visibilitas Akses Konsumen - Pratama, Ega; Afriansyah, Rizki; Perdiana, M Raka; Julinda, Asok; Rosalia, Rosalia; Amriansyah, Ahmad (-, 2026)
Micro, Small, and Medium Enterprises play an important role in the rural economy, yet they still face challenges related to business visibility and consumer access. Many rural MSMEs have not adopted digital technology, which makes their businesses difficult to find and limits their transaction systems. This community service activity aimed to promote the digitalization of MSMEs in Lekis Rejo Village Block K through business location mapping on Google Maps, implementation of a QRIS based digital payment system, and the creation of business banners as visual promotional media. The implementation method used descriptive and participatory approaches by directly involving MSME actors at every stage of the activity. The activity procedures included initial observation, socialization, assistance in business mapping, QRIS implementation, banner creation, as well as monitoring and evaluation. The results showed that all partner MSMEs were registered on Google Maps, were able to use QRIS as a payment method, and had business banners as visual identities. The evaluation indicated an increase in MSME actors’ understanding of business digitalization and a more open attitude toward the use of technology. This activity had a positive impact on improving business visibility and consumer access, and it supported the sustainable strengthening of rural MSMEs.